The Movie Mogul, Moses and Muslims Islamic Elements in Cecil B. DeMille’s The Ten Commandments (1956) - Calabria, Michael D. (2015)
Cecil B. DeMille’s 1956 film, The Ten Commandments, has come to define the genre of the biblical epic. It has earned a permanent place in American culture due to its annual airing on television during the Easter and Passover holidays. Most viewers are unaware, however, that DeMille had sought to make a film that would appeal to Jews, Christians and Muslims at a time when their common Abrahamic ancestry had yet to be articulated, and interreligious dialogue was all but unheard of. To this end, Henry Noerdlinger, DeMille’s researcher for the film, consulted the Qur’an, and screenwriters incorporated Islamic references into the script. This article explores the social and historical context for the film, Noerdlinger’s published volume of research (Moses and Egypt) and examines those parts of the script with explicit references to the Qur’an and Muslims.
Keywords: DeMille -- Ten Commandments -- Qur'an -- Islam -- Muslims